A regenerative 3D scaffold for inguinal hernia repair. MR imaging and histological cross evidence. Qualitative study. (December 2021) - Amato, Giuseppe; Agrusa, Antonino; Puleio, Roberto; Micci, Giuseppe; Cassata, Giovanni; Cicero, Luca; Di Buono, Giuseppe; Calò, Pietro Giorgio; Galia, Massimo; Romano, Giorgio
Abstract: Background: Inguinal hernia is a degenerative disease occurring in a high motile surround. Stopping degeneration and promoting tissue regeneration should be the treatment goal. Groin hernias are conventionally managed with static flat meshes, mostly fixated to the delicate inguinal environment. Far from a regenerative effect, the biologic response of conventional hernia meshes is characterized by a foreign body reaction leading to a stiff/shrunken scar plate, which is often the source of unpleasant complications. Recently, a newly engineered 3D device for inguinal hernia repair – ProFlor-has been developed to produce a regenerative biological response. Unlike conventional hernia meshes, this regenerative 3D hernia scaffold seems to demonstrate suitable features for a pathogenetical and physiological coherent treatment of the disease. The aim of this manuscript is to cross evidence these features through magnetic resonance imaging (MRI) and histology. Study design: The biological response of ProFlor at three defined post-implantation stages has been evaluated through MRI signal intensity and compared to neighbouring muscles and fat. As additional proof, histology of tissue specimens excised at the same post-implantation periods from porcine models during an experimental attempt were also evaluated. Results: MRI of newly ingrown tissue in ProFlor demonstrated similar signal intensity of muscles while fat tissue showed remarkably higher values. These data matched with the histology of ProFlor biopsies excised from pigs. Conclusions: The motile compliance to groin movements of ProFlor appears to induce a probiotic biologic response comparable to a regenerative scaffold, allowing to physiologically resolve the degenerative source of inguinal hernia disease. Highlights: MRI evidence of regenerative effect in 3D scaffold for inguinal hernia repair ProFlor in the short, mid and long term post-implantation. Enhanced biological response into the 3D inguinal hernia scaffold ProFlor histologically verified in porcine experimental model. Regenerative biologic response of ProFlor results pathogenetically coherent for the cure of the degenerative damages caused by inguinal hernia disease.